Voices Unheard: Teachers' Perspectives on Students' Speaking Challenges in the Classroom - Harmawati, Fifi; Ilma, Ridha; Amrina, Rizqy Dwi (The Art of Teaching English as a Foreign Language (TATEFL), 2024)
This qualitative study examines the challenges that students at a private Islamic junior high school in Palembang encounter when learning to speak, with an emphasis on the viewpoints of the teachers. Data collection involved structured interviews and classroom observations to gather insights into students' challenges. Participants included teachers and students selected through purposeful sampling. Thematic analysis was employed to analyze the data, revealing themes such as students' fear of making mistakes, difficulty in language comprehension, and the use of native language in learning. The importance of fostering a positive and inclusive learning atmosphere where students feel comfortable taking linguistic risks and expressing themselves freely is emphasized in the conclusion. Strategies such as providing targeted instruction in phonetics and vocabulary, and balancing the use of the native language to support English language acquisition, are essential. This research contributes to understanding the complexities of language learning and provides insights for educators to enhance students' speaking skills effectively